Sub‐maximal aerobic exercise training reduces haematocrit and ameliorates symptoms in Andean highlanders with chronic mountain sickness. Issue 11 (30th September 2021) - Macarlupú, José Luis; Vizcardo‐Galindo, Gustavo; Figueroa‐Mujíca, Rómulo; Voituron, Nicolas; Richalet, Jean‐Paul; Villafuerte, Francisco C.
Abstract : New Findings: What is the central question of this study? What is the effect of sub‐maximal aerobic exercise training on signs and symptoms of chronic mountain sickness (CMS) in Andean highlanders? What is the main finding and its importance? Aerobic exercise training (ET) effectively reduces haematocrit, ameliorates symptoms and improves aerobic capacity in CMS patients, suggesting that a regular aerobic ET programme might be used as a low‐cost non‐invasive/non‐pharmacological management strategy of this syndrome. Abstract: Excessive erythrocytosis is the hallmark sign of chronic mountain sickness (CMS), a debilitating syndrome associated with neurological symptoms and increased cardiovascular risk. We have shown that unlike sedentary residents at the same altitude, trained individuals maintain haematocrit within sea‐level range, and thus we hypothesise that aerobic exercise training (ET) might reduce excessive haematocrit and ameliorate CMS signs and symptoms. Eight highlander men (38 ± 12 years) with CMS (haematocrit: 70.6 ± 1.9%, CMS score: 8.8 ± 1.4) from Cerro de Pasco, Peru (4340 m) participated in the study. Baseline assessment included haematocrit, CMS score, pulse oximetry, maximal cardiopulmonary exercise testing and in‐office plus 24 h ambulatory blood pressure (BP) monitoring. Blood samples were collected to assess cardiometabolic, erythropoietic, and haemolysis markers. ET consisted of pedalling exercise in a cycloergometer at 60% of V ̇ O 2 peak for 1 h/day, 4 days/week for 8 weeks, and participants were assessed at weeks 4 and 8. Haematocrit and CMS score decreased significantly by week 8 (to 65.6 ± 6.6%, and 3.5 ± 0.8, respectively, P  < 0.05), while V ̇ O 2 peak and maximum workload increased with ET (33.8 ± 2.4 vs. 37.2 ± 2.0 ml/min/kg, P  < 0.05; and 172.5 ± 9.4 vs. 210.0 ± 27.8 W, P  < 0.01; respectively). Except for an increase in high‐density lipoprotein cholesterol, other blood markers and BP showed no differences. Our results suggest that reduction of haematocrit and CMS symptoms results mainly from haemodilution due to plasma volume expansion rather than to haemolysis. In conclusion, we show that ET can effectively reduce haematocrit, ameliorate symptoms and improve aerobic capacity in CMS patients, suggesting that regular aerobic exercise might be used as a low‐cost non‐invasive and non‐pharmacological management strategy.